Chan Texts in Practice: Towards a Socio-Historical Approach to Early Chan - Van Schaik, Sam (Journal of Chan Buddhism, 2021)
Research into early Chan has relied heavily on the manuscripts found in Cave 17 in Dunhuang, which generally date from before the eleventh century. However this research has often abstracted texts from their context as part of the varied and multilingual collection that was found in the cave. Furthermore, the date, form and original use of the manuscripts containing early Chan texts is often forgotten in the discussion. This brief paper looks at early Chan practice from a historical and local perspective, that is, as a kind of social history. Taking one text, The Record of the Masters and Students of the Lanka (Lengqie shizi ji 楞伽師資記) I discuss some of the meditation practices that it contains and compare these to manuscripts from the Dunhuang collection that fall outside the usual concept of ‘Chan Buddhism’. I conclude that first, early Chan texts should be understood as existing in specific social and ritual settings, such as group initiation rituals, educational settings with teachers and students, or indeed solitary meditation. Second, in the social setting that produced the Dunhuang manuscript cache, distinctions between what we tend to think of as ‘Chan meditation’ and other forms of meditation from tantric or pure land contexts, meant little in practice.